Perbaikan Alur Proses pada Fungsi Yang Terkait dalam Meningkatan Efektifitas Manajemen Rantai Suplai pada Fungsi Pengadaan : Studi Kasus Di Divisi Manufaktur Peralatan Kamar Mandi (Plumbing-Fitting) PT. Surya Toto Indonesia Tbk - Hakim, Andi; Revino, Revino (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2022)
There is a background in the Plumbing-Fitting industry from PT. Surya Toto Indonesia Tbk which was taken over a period of 3 years, namely 2017 - 2019. From the data collected, it turns out that every year there are problems that always recur, seen with the flow of processes and supply chain effectiveness from the functions of the PPIC, Incoming QC, Customer (Vendor) Departments. and Warehouse Incoming where the problem always existed in those years. Researchers try to approach the problem with an approach that uses tools or tools sequentially, including: Business Process Improvement, Nominal Group Technique, Pareto Diagram, Fishbone Diagram, Process Hierarchy Analysis, Long Term Relationship, which in turn is the solution of the management tool. will be applicable to the SAP system. The success of the process flow approach and supply chain management carried out here will affect the effectiveness of the procurement function with improvements to the 4 right concept, namely on time, right quantity, right price, right quality thus, 4 problems that always recur in the 2017-2019 period it will become decreased and potentially lost. The process flow improvement can be done by adding a Field to the SAP system and this is very beneficial for the PPIC and Marketing Department, while for the improvement of 3 claims from the Incoming QC Department, QC Customer (Vendor) and Incoming Warehouse by making a T-Code Detail Claim Information which later on the claim requestion will appear as a Summary Compalin Report on the SAP system so that it replaces the work process with manual software. Furthermore, the relationship between the Procurement function and the 4 problems mentioned above is that the relationship can be improved by fixing the problem of canceling the goods finish schedule and reducing the other 3 claims.